Waqf Sukuk as an Alternative Financing Instrument for Specialized Health Services: within the Islamic Health Insurance System - Ayu Qamariya; Muhaimin, Abd. (IAIN Batusangkar, 2025)
The National Health Insurance (JKN) program managed by BPJS Kesehatan aims to achieve equitable healthcare services for all Indonesian citizens. However, in its implementation, this system still faces serious obstacles related to funding sustainability, such as recurring budget deficits and delays in payment of claims to healthcare facilities. This situation demonstrates the urgency of finding a more stable alternative funding source. This qualitative research using a desk study method offers Cash Waqf Linked Sukuk (CWLS) or sukuk waqf as an innovative solution to strengthen the sharia-based healthcare financing system. The results reveal that the integration of sukuk investment instruments and the philanthropic values of waqf can create a productive financing model while having a strong sociospiritual impact. Theologically, the implementation of CWLS supports the principles of maqasid al-shari'ah, particularly in safeguarding life (hifz al-nafs) and wealth (hifz al-mal). Despite its great potential, the implementation of sukuk waqf in the health sector still faces real challenges, including limited regulations, low levels of Islamic financial literacy in the community, and suboptimal institutional coordination between the government, financial institutions, and waqf management bodies